2022
DOI: 10.1101/2022.10.31.514480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SMDT1variants impair EMRE-mediated mitochondrial calcium uptake in patients with muscle involvement

Abstract: Ionic calcium (Ca2+) is a key messenger in signal transduction and its mitochondrial uptake plays an important role in cell physiology. This uptake is mediated by the mitochondrial Ca2+ uniporter (MCU), which is regulated by EMRE (essential MCU regulator) encoded by the SMDT1 (single-pass membrane protein with aspartate rich tail 1) gene. This work presents the genetic, clinical and cellular characterization of two patients harbouring SMDT1 variants and presenting with muscle problems. Analysis of patient fibr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Although no MCU mutation has ever been identified in humans, a recent preprint by Bulthuis et al [ 71 ] reported two patients with EMRE mutations that lead to a loss of EMRE protein. Muscle breakdown was a common phenotype observed in both patients, who otherwise showed diverse symptoms.…”
Section: Expanding the Functions Of Mitochondrial Ca2 + ...mentioning
confidence: 99%
“…Although no MCU mutation has ever been identified in humans, a recent preprint by Bulthuis et al [ 71 ] reported two patients with EMRE mutations that lead to a loss of EMRE protein. Muscle breakdown was a common phenotype observed in both patients, who otherwise showed diverse symptoms.…”
Section: Expanding the Functions Of Mitochondrial Ca2 + ...mentioning
confidence: 99%
“…The importance of mitochondria in shaping Ca 2+ -signals has been long known (Rizzuto et al, 2012) and it is also likely that this increased Ca 2+ also alters mitochondrial bioenergetics, although we did not directly investigate it. In skeletal muscle, the importance of mitochondrial Ca 2+ is less characterized than in other cell types but is important to note that mutations of the proteins involved in mitochondrial Ca 2+ -transport have been very recently shown to lead to muscle dysfunction (Bulthuis, et al, 2022) providing evidence that this mechanism is highly relevant.…”
Section: Bitter Agonist Induces Relaxation Effect On Usc-skmcsmentioning
confidence: 99%